Cerai Ṭhalaq di Kalangan Isteri Karier: Studi Kasus di Mahkamah Syar’iyah Banda Aceh (Divorce of Ṭhalaq among Career Wives: Case Study in Banda Aceh Syar'iyah Court) - Devy, Soraya; firdaus, muhammad (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2019)
Women's current career many filed for divorce ṭhalaq. One of the matters of divorce Ṭhalaq towards a career wife occurred at the Court of Shar'iyah in Banda Aceh. The problem in this article is what is the reason for the divorce Ṭhalaq to a career wife that is found in the ruling on the court of the city of Bnada in Aceh and how Fiqh ṭhalaq review of divorce Ṭhalaq wife career. To answer the problem is conducted a research through normative juridical approach by researching the library material or secondary data As a base material on the rules and literature relating to the issues studied. The results of this study showed that the reasons for his divorce in his career wife on the verdict in this thesis is the occurrence of affair done by the wife, syiqaq, Nusyuznya wife, selfishness wife, and the abandonment of the child. As for the Fiqh review of divorce in the career of the wife who Nusyuz got threats from Allah, including the wife of his rights in the Nusyuz period. The three stages that must be passed to face the wife Nusyuz. First The husband must rebuke and asunder his wife. Second, Suamimelakukan The effort to split the bed. And the third husband may hit his wife with a blow that does not hurt his wife and leaves no marks.